Narraciones y experiencias literarias en el Valle del Cauca - Zamudio Tobar, Gladys; Rosas Consuegra, Adriana; Bejarano, Alberto; Cuartas Montero, Deisy; Bravo Baeza, Rodrigo; Villa Castaño, Sandra Patricia; Giraldo Ramírez, Germán (Universidad Santiago de Cali, 2022)
Published